1994
DOI: 10.1111/j.1365-2621.1994.tb06885.x
|View full text |Cite
|
Sign up to set email alerts
|

Fat Level, High Temperature Cooking and Degree of Doneness Affect Sensory, Chemical and Physical Properties of Beef Patties

Abstract: Ground beef patties containing either 4 or 20% fat were cooked by electric grill (G) alone or in combination with overhead broiler unit (BG) to be (visually) either medium or well-done. Patties with 20% fat had higher beef flavor intensity, juiciness and tenderness scores, lower Instron shear and compression values, and lower cooking yields than 4% fat patties., However, 4% fat patties cooked to medium, had similar sensory ratings to 20% fat patties cooked well-done. About 20% of patties cooked to medium did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
1
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 13 publications
11
82
1
2
Order By: Relevance
“…Troutt et al (1992a) and Troutt et al (1992b) demonstrated that lower fat formulations had increased hardness values using a texture profile analysis method similar to that in the current study. Fat level has been reported to affect other textural values, with increased fat level resulting in lower cohesiveness, gumminess, and chewiness values, with little impact on springiness, as fat increased from 4 to 20% (Berry, 1994). These trends for textural properties and increased fat level were demonstrated in the current study as well with samples formulated to have fat percentages ranging from 10 to 27%.…”
Section: Objective Texture Measurement and Shear Valuessupporting
confidence: 61%
“…Troutt et al (1992a) and Troutt et al (1992b) demonstrated that lower fat formulations had increased hardness values using a texture profile analysis method similar to that in the current study. Fat level has been reported to affect other textural values, with increased fat level resulting in lower cohesiveness, gumminess, and chewiness values, with little impact on springiness, as fat increased from 4 to 20% (Berry, 1994). These trends for textural properties and increased fat level were demonstrated in the current study as well with samples formulated to have fat percentages ranging from 10 to 27%.…”
Section: Objective Texture Measurement and Shear Valuessupporting
confidence: 61%
“…However, research has found that some fat substitutes composed of carbohydrates like starches and fibers, among others, can improve the physical and sensory characteristics of meat products with reduced fat when used at concentrations of up to 3 % (Berry 1994;Desmond et al 1998;Troy et al 1999;Anderson and Berry 2000). It is also important to note that meat does not contain fiber and is frequently associated with the appearance of diseases in the human digestive tract (Mansour and Khalil 1997).…”
Section: Introductionmentioning
confidence: 99%
“…These thawing methods are time consuming and require external heating, after which change in the quality of the meat occur (Kang et al, 2007). Changes which take place during the thawing processes of frozen meat include the growth of microorganisms, weight loss due to drip loss, and color change (Berry, 1994; Kondratowicz et al, 2008), effect of WHC (Miller et al, 1980;Sebranek, 1979;Zhuang, 2012), increase of rancidity (Lannari and Zaritzky, 1991;Sebranek et al, 1978), denaturation of protein (Wagner and Anon, 1985;Wagner and Anon, 1986) and softening of tissues, which results in a changes which are quite apparent to the consumer (Fennema, 1973;Jason, 1974;Kim et al, 1990).…”
Section: Introductionmentioning
confidence: 99%